Thai Immigrant Service-based Entrepreneurship in the UK: Mixed Embeddedness, Superdiversity, and Combined Ethnic and Non-Ethnic Capital - Sirijit Sunanta (Advances in Southeast Asian Studies, 2022)
This paper examines Thai immigrant entrepreneurship in the UK, drawing on 17 inter-views with Thai migrants in Brighton, East Sussex. It explores how Thai immigrants from different socioeconomic backgrounds and migration pathways mobilize ethnic and non-ethnic forms of capital in their entrepreneurial activities. Thai immigrants constitute a relatively new, small, but internally diverse migrant population in the UK, with female marriage migrants dominating the Thai migrant population in the past two decades. The findings of this study reveal that Thai migrants tend to own small-scale businesses or provide personal services in three sectors: cleaning and care work, beauty and massage, and food and catering. In their interaction with opportunity structures in the UK, Thai restaurant and massage entrepreneurs mobilize the exotic notion of “Thai-ness” to add value to their services catering to local British customers.